Discovery discover classical music with the Sydney Symphony and Richard Gill. - Beethoven, Ludwig van.; Gelmetti, Gianluigi; Gill, Richard; Haydn, Joseph; Mozart, Wolfgang Amadeus; Sydney Symphony Orchestra ([Australia] : ABC Classics, 2007)
Beethoven for beginners? Mozart for the musically - challenged? Haydn highlights package? This is the series that lets even the muscial novice into the inner circle of these three superstars of their time - the 'holy trinity' of classical composers. Acclaimed conductor Richard Gill uncovers the genius of these great musicians with his 'plain English' dissection of four of their most-loved symphonies.
Beethoven, Symphony No. 5: Movement I, Allegro conbrio -- Haydn, Symphony No. 94 (Surprise): Movement II, Andante -- Mozart, Symphony No. 35 (Haffner): Movement I, Allegro con spirito -- Beethoven, Symphony No. 7: Movement II, Allegretto.
Richard Gill ; Sydney Symphony Orchestra, chief conductor & artistic director, Gianluigi Gelmetti.
Keywords: Musical films; Documentary films